Myth and Identity: A Compilation of Oral Traditions in a University Context from Peru - Marino-Jiménez, Mauro (2023)
Peru is a multicultural country, with a wide wealth of languages and traditions. However, most of the contributions from the Andean and Amazon areas have suffered segregation by members of the majority culture, represented by the Spanish language and centralised in the coastal cities. For this reason, migration to these territories has included the concealment of the mother tongue, cultural mimicry and the loss of identity values. For this reason, this study seeks to achieve the opposite effect: to revalue the Quechua language through the presentation and compilation of oral myths from different Andean localities, thanks to the conception, performance and style of a group of students of the Beca 18 program at a private university from Lima. This means revaluing the cultural elements that are part of the identity of these students, specifying the activity as a form of cultural strengthening, and recovering the myth as a manifestation of oral literature in the Peruvian environment, as well as in the official spaces of culture majority.